Improved pseudocapacitive performance of well-defined WO3−x nanoplates. Issue 3 (April 2015) - Lee, Seul; Lee, Young-Woo; Kwak, Da-Hee; Kim, Min-Cheol; Lee, Jin-Yeon; Kim, Da-Mi; Park, Kyung-Won
Abstract: We demonstrate the well-defined tungsten suboxide nanoplates for pseudocapacitors via a low-temperature reduction reaction under hydrogen gas atmosphere. The as-prepared WO3− x reduced at 500 °C using WO3 nanoplates (500-WO3− x ) shows a pure monoclinic structure and single crystalline nanoplates. The 500-WO3− x exhibits much improved pseudocapacitive performance due to W 5+ and W 4+ oxidation states obtained by a reduction process and improved electrical conductivity.